Phoneme class recognition and automatic syllabification with a phonological based hidden Markov model - Prinsloo, Gerhardus Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1988.